Knowledge, Attitude and Practice regarding Human Papilloma Virus Vaccine among Adolescents in Bharatpur Metropolitan City, Chitwan, Nepal - Koirala, Sushila; Sharma, Sarojini; Upadhyay, Hari Prasad; Dhital, Pratikshya (Nepalese Journal of Cancer, 2025)
Background: Human papillomavirus (HPV) infection is a main cause of cervical cancer. Cervical cancer kills one woman every two minutes and those in low- and middle-income countries tend to bear a disproportionate burden (90%) of cervical cancer, most cases of which are caused by the human papillomavirus (HPV) that is preventable by vaccine.Materials and Methods: A descriptive cross-sectional study was carried out to assess the knowledge, attitude and practice regarding Human Papilloma Virus Vaccine among 256 adolescents who were studying at Grade11 and 12 selected by non-probability purposive sampling technique. The setting of the study was two private and two public schools of Bharatpur metropolitan which were selected randomly. Data was collected by using self-administered structured questionnaires from June to August, 2024 and analyzed by using both descriptive and inferential statistics through Statistical Package for Social Science (SPSS) version 22. Findings: Despite all of the school adolescents had positive attitude regarding HPV vaccine, more than four fifth of adolescents (83.6%) had poor level of knowledge, 12.9% had moderate level of knowledge and only 3.5% had good knowledge regarding HPV infection and HPV vaccine. About one fourth (25.4%) had received HPV vaccine so majority (74.6%) of adolescents had poor practice. The findings of this study also revealed that there was association between the level of knowledge and occupation of parents (p=0.000).Conclusion: This study concludes that though all adolescents have positive attitude regarding HPV vaccine they have still poor knowledge and practice. As the study participants’ knowledge on HPV and HPV vaccine is crucial, influencing their recommendations to the general public, their family, friends thus impeding the acceptance of the HPV vaccination.